A one-step graphene induction strategy enables in-situ controllable growth of silver nanowires for electromagnetic interference shielding. (15th October 2021) - Jia, Hui; Yi, Zong-Lin; Huang, Xian-Hong; Su, Fang-Yuan; Kong, Qing-Qiang; Yang, Xiao; Wang, Zheng; Xie, Li-Jing; Guo, Quan-Gui; Chen, Cheng-Meng
Abstract: The introduction of silver nanowires (AgNWs) with high electrical conductivity into graphene skeletons significantly enhances its electromagnetic shielding performance. However, the complicated procedures and low yield of the AgNWs preparation and the lack of strong interaction between graphene and AgNWs by physical self-assembly method limits the electromagnetic shielding application. Herein, a one-step graphene induction strategy without other nucleating and morphology agents of halide ion is exploited for the in-situ synthesis graphene/AgNWs composite. The O=C–O groups of graphene provide a nucleation site to combine Ag nucleus. Importantly, graphene with oxygen functional groups acts as an "Ag + pool" to store and release abundant Ag +, supplying consecutively Ag + for AgNWs growth and inhibiting excessive nucleation. Benefiting from the high ohmic loss of 3D conductive network, the resulting graphene/AgNWs coating exhibits remarkable electromagnetic shielding effectiveness of 76.59 dB. This provides a broad prospect for the as high-performance electromagnetic shielding materials. Graphical abstract: A one-step graphene induction strategy was developed for in-situ synthesis of Ag NWs and Ag NPs. The graphene-induced nucleation mechanism shows that the nucleation site from O=C–O groups of graphene. It was proposed that graphene with oxygen functional groups acts as an "Ag + pool" to control the Ag + concentration in the Ag NWs growth. The resulting graphene/Ag NWs composite coating exhibits an excellent EMI SE of 76.59 dB. Image 1 Highlights: A one-step graphene inducted strategy is exploited for in-situ controllable synthesis of Ag NWs. The O=C–O group of graphene provides a nucleation site to combine Ag nucleus. An Ag NWs formation mechanism is proposed with graphene-induced nucleation, growth and ripening. The resulting graphene/Ag NWs coating exhibits an excellent electrical conductivity and EMI SE in X-band.